ChemInform Abstract: A Novel Sb2Te3 Polymorph Stable at the Nanoscale. Issue 35 (September 2015) - Rotunno, Enzo; Longo, Massimo; Wiemer, Claudia; Fallica, Roberto; Campi, Davide; Bernasconi, Marco; Lupini, Andrew R.; Pennycook, Stephen J.; Lazzarini, Laura
Abstract Self‐assembled Sb2Te3 nanowires with diameters of <40 nm are grown on a Si wafer coated with a 50 nm SiO2 layer in a thermal MOCVD reactor using (Me2N)3Sb and iPr2Te as precursors in the presence of (Me2N)4Ge.